PELATIHAN DIGITAL MARKETING DAN DESIGN BRANDING UNTUK UMKM DESA NGENEP, KABUPATEN MALANG - Erlangga Setyawan; Andira Dwi Wiranugraha; Muhamad Ziauddin Ulya; Anindyta Nur Fatimah; Syahnaz Twosya Salam; Anugrah Christin Yunita (Wisesa: Jurnal Pengabdian Masyarakat, 2025)
Limited digital skills remain a significant challenge for micro, small, and medium enterprises (MSMEs) in rural areas, including in Ngenep Village, Malang Regency. This community service activity aims to enhance the capacity of MSME actors in digital marketing strategies and branding design, which have been major obstacles in expanding markets and strengthening product identity. The program was conducted using a participatory approach involving 42 female PKK cadres as training participants. Activities included field observation, problem identification, module development, interactive training, and evaluation through quizzes and group discussions. The results showed increased understanding and skills among participants, particularly in designing promotional content using Canva. The outputs included a training module, digital branding templates, visual documentation, and strategic recommendations. This program demonstrates that needs-based training can effectively support the competitiveness of rural MSMEs in the digital economy. The findings also highlight the importance of continued technical assistance and digital infrastructure support to ensure sustainable digital transformation.